Role of Serum Ferritin in Predicting Outcomes of COVID-19 Infection Among Sickle Cell Disease Patients: A Systematic Review and Meta-Analysis - Lee, Jun Xin; Chieng, Wei Keong; Abdul Jalal, Muhammad Irfan; Tan, Chai Eng; Lau, Sie Chong Doris (Frontiers in Medicine, 2022)
Patients with sickle cell disease (SCD) are at higher risk of getting severe COVID-19 infection. This systematic review and meta-analysis aimed to determine the role of serum ferritin in predicting ICU admission and mortality among patients with SCD following COVID-19 infection. A systematic search was conducted in PubMed, Scopus, Web of Science, Embase, WHO COVID-19 database, ProQuest and Cochrane Library for articles published between 1st December 2019 to 31st November 2021. Methodological quality was assessed using Joanna Briggs Institute (JBI) critical appraisal checklists. Eleven articles (7 cohorts and 4 case series) were included in this review. Pooled mean serum ferritin level on admission was 1581.62 ng/mL while pooled proportion of ICU admission and mortality were 0.10 (95% CI 0.06;0.16, prediction interval 0.04;0.23, p=0.29, I2=17%) and 0.07 (95% CI 0.05;0.11, prediction interval 0.04;0.12, p=0.68, I2=0%) respectively. Meta-regression showed that serum ferritin did not predict for both ICU admission (regression coefficient=0.0001, p=0.3523) and mortality (regression coefficient=0.0001, p=0.4029). Our analyses showed that serum ferritin may not be a useful marker to predict the outcomes of COVID-19 infection among patients with SCD. More data are required to identify a reliable tool to identify patients with SCD who are at risk of getting severe COVID-19 infection.